Physical and Adsorptive Characterization of Precipitated Magnesium Silicate from Rice Hull Ash Silica - KIRAN YILDIRIM, BERÇEM; SAYAN, PERVİZ; SARGUT, SİBEL (WILEY-V C H VERLAG GMBH, 2011)
Precipitation of magnesium silicate from sodium silicate and MgCl2 and MgSO4 solutions was investigated at four different reactant feed rates and two temperatures (25 degrees C and 50 degrees C). Sodium silicate solutions were produced from rice hull ash silica. The final product was characterized by scanning electron microscopy, X-ray diffraction, thermogravimetric analysis/differential thermal analysis, crystal size distribution, and filtration rate measurements. Physical characteristics of the studied magnesium silicates were determined by the Brauner-Emmett-Teller method and their adsorption capacities were compared to commercial magnesium silicate (Florisil). The adsorption was spontaneous and endothermic. The best fit of the kinetic results was achieved by a pseudo-second-order equation. The equilibrium data were found to be well represented by the Freundlich isotherm equation.
Keywords: Adsorption; Adsorption isotherms; Adsorption kinetics; Magnesium silicate; SORPTION; REMOVAL; CADMIUM; TALC